1975
DOI: 10.1007/bf00377586
|View full text |Cite
|
Sign up to set email alerts
|

Perturbation analysis of competition and overlap in habitat utilization between Dipodomys ordii and Dipodomys merriami

Abstract: The populations of two coexisting species of Dipodomys (Heteromyidae, Rodentia) were manipulated on 10, large, unenclosed, trapping grids. These manipulations revealed that, although many kangaroo rats are established residents in an area, a large number are transient individuals who quickly occupy vacated habitats. On plots from which residents had been removed, transients settled at rates of up to 5% of carrying capacity per day. These immigrants were invariably of the same species that was removed, indicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
107
2

Year Published

1977
1977
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(116 citation statements)
references
References 18 publications
7
107
2
Order By: Relevance
“…The competitive nature of the interaction was suggested by increase in the number of Perognathus in response to removal of Dipodomys. This result is contrary to that found by Schroder and Rosenzweig (1975) who found no density response between two species of Dipodomys of very similar size. In addition, the quick increase of the number of Perognathus to the removal of Dipodomys differs from the findings of Munger and Brown (1981) were it took 8 months for the small rodents to increase in number in response to the removal of Dipodomys.…”
contrasting
confidence: 99%
See 2 more Smart Citations
“…The competitive nature of the interaction was suggested by increase in the number of Perognathus in response to removal of Dipodomys. This result is contrary to that found by Schroder and Rosenzweig (1975) who found no density response between two species of Dipodomys of very similar size. In addition, the quick increase of the number of Perognathus to the removal of Dipodomys differs from the findings of Munger and Brown (1981) were it took 8 months for the small rodents to increase in number in response to the removal of Dipodomys.…”
contrasting
confidence: 99%
“…Schroder and Rosenzweig (1975) removed rodents from large study plots with the surprising result that little competition exists between two coexisting species of similar size. They concluded that competition had been important in the past, but is not presently affecting interspecific interactions.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Dayton (1973) showed that patterns consistent with 2 aspects of competition theory actually had quite different causes. Schroder & Rosenzweig (1975) tested previous ideas that 'habitat specializat i o n~, food habits, and species diversity of desert rodents . .…”
Section: T Purpurascens (Mcguinness 1987bmentioning
confidence: 98%
“…Hence, there appears to be a limit to how far the community can compensate for the absence of certain species. Among the possible explanations for this might be that assemblages of desert rodents have been associating together for a sufficient time to have lost the flexibility to respond to situations where one or more of the species are absent (Schroder and Rosenzweig 1975). Another is that quadrupedal species may have a limited ability to avoid predators in open microhabitats and this limits the degree to which they can compensate when the bipeds are removed.…”
Section: Removalmentioning
confidence: 99%